SISTEM PENERIMAAN KARYAWAN BARU MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) BERBASIS ANDROID - Abdurrahman Abdurrahman; Firmansyah Firmansyah (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2018)
Employees are those who work specifically for businesses or companies both government and government and provide employee benefits in accordance with the regulations that apply both daily, weekly and monthly Acceptance of new employees or recruitment is important for the company to get new recruits in a position. Recruitment is essentially the process of determining and attracting applicants who are able to work within a company. This process begins for applicants who are sought and end by combining their applications or collected. Obtained a group of applicants for prospective new employees to be selected and selected In some companies, the process of receiving new employees is still done manually. This happens because there is no systematic standard method to assess the feasibility of prospective new employees. With the application of a decision support system for new employee recruitment that was built using the Simple Additive Weighting (SAW) method. This method is chosen because it can determine the weight value for each attribute, then proceed with the ranking process that will select the best alternative from a number of alternatives, in this case the alternative in question is the one who has the right to be accepted as a new employee based on the specified criteria. Based on the results of the testing, the system that is built can facilitate and accelerate the process of selecting new employee recruitment and assist the division manager of Human Resources in making decisions to determine new employees in a company Keywords: employee, Acceptance of New Employees, SAW